Study of distribution of beta-pollution in the city of Almaty - Dyachkov, V.V.; Zaripova, Yu.A.; Yushkov, A.V.; Shakirov, A.L.; Bigeldiyeva, M.T.; Dyussebayeva, K.S.; Abramov, K.E. (Recent Contributions to Physics, 2018)
The present work is devoted to the study of the distribution of beta activity of natural radionuclides in the surface soil of Almaty in the spring. The soil samples were collected during the period April-May 2018 in different parts of the city of Almaty. Sample preparation of soil samples was limited to soil selection, which was dried overnight, crushed, its residual moisture was measured, and its beta spectrum was further measured. The exposure time of the measurements of one spectrum averaged 90 minutes. In addition to the background beta particles generated by cosmic rays, the influence on the intensity of the beta spectrum is exerted by the existence of temporal variations in radon emanation, and within a day the radon activity in air can vary in a relatively wide range. Consequently, the concentration of daughter decay products (DDPR) on aerosols of air will affect the background of beta particles. In this connection, after each measurement of the soil sample, background spectra of beta particles were measured. As a result of the performed measurements and analysis of the intensity distribution of beta contamination of surface soil in different parts of Almaty, the emergence of radionuclide radionuclides of radon DDPR in the surface layer of the atmosphere and atmospheric precipitation was determined, which is mainly due to aerosol particles. In turn, radon atoms emanating from the lower soil layers coagulate with aerosol particles. The degree of concentration of beta radionuclides of radon DDPR depends on the chemical composition of the soil cover, on meteorological conditions and on its own chemical properties, on which the ability of migration and accumulation in the surface soil layer depends. The obtained integral values of beta radionuclides of radon DDPR show the spatial fractal spread and correspond to the literature data taking into account abundant precipitation during the sampling period.